The National Games and national identity in China : a history / Liu Li and Fan Hong. - Liu, Li, 1986-; Fan, Hong, 1957- (Routledge focus on sport, culture and society, 2017)
The history of China's National Games reflects both the transformation of elite sport in China and wider Chinese society. This is the first book to describe the origins and development of the National Games through their dynamic relationship with Chinese politics, nationalism and identity in the modern era.